Management of Unbled Brain Arteriovenous Malformation Study - Mohr, JP. (Neurol Clin, 2015)
In a recently-reported NINDS-funded randomized clinical trial, the first for brain arteriovenous malformations, limited to those discovered not having bled, medical management alone was found superior to medical management plus intervention to eradicate brain arteriovenous malformations. The trial was halted at the recommendation of the NINDS-appointed Data and Safety Management Board after 226 randomizations and a mean follow-up of 3.3 years due to a disparity favoring the medical arm (HR=3.41 95%CI: 1.72-6.76). Patients eligible for the trial were selected by the interventional teams as suitable for lesion eradication. The initial sample size of 800 and follow-up plans for mean 7 years were lowered and shortened, respectively, by the outcome data. An application for extended follow-up was given poor priority scores by a NINDS Study Section and Council due to estimations the disparities in outcomes would not change significantly.